Marketing and managing tourism destinations - Morrison, Alastair M. (Routledge, 2013)
"Marketing and Managing Tourism Destinations is a comprehensive and integrated textbook which uniquely considers both destination marketing and management in one volume. It focuses on how destination marketing is planned, implemented and evaluated as well as the management and operations of destination marketing and management organizations, how they conduct business, major opportunities, challenges and issues they face to compete for the global leisure and business travel markets."--Provided by publisher.